High level of interleukin-10 in serum after therapy is characteristic of prostate carcinoma patients with high Gleason score, high tumor volume and present peritumoral infiltration - Jovanović, Dejan; Bančević, Vladimir; Jovanović, Vanja; Šupić, Gordana; Abazović, Džihan; Stanojević, Ivan; Vojvodić, Danilo (Vojnosanitetski pregled, 2021)
Background/Aim. Recent data imply the significance of certain cytokines in the appearance and development of prostate cancer (PC), as well as their association with pathohistological and/or clinical characteristics of PC. The aim of this study was to examine the relationship between the IL-10 concentration with histopathological and clinical characteristics of PC patients. Methods. IL-10 concentration was determined in serum, urine and prostate massage secret (pms) samples of 88 CP patients (initially and after therapy), 20 benign prostatic hyperplasia (BPH) patients and 15 healthy controls. Results. Compared to BPH and control groups, PC patients had the highest average serum IL-10 concentration. Interestingly, BPH patients demonstrated the highest concentration of IL-6 in urine and pms samples. Also, patients with G3 gradus and with the highest Gleason score (4 + 4) demonstrated the highest IL-10 serum level. PC patients without any histopathological sign of tumor invasion had a significantly increased serum IL-10, either before or after the therapy, compared to the patient group with evident invasion of tumor cells. The therapy induced different IL-10 profile in serum and urine samples. After the therapy, there was a clear significant IL-10 increase in serum of patients with unfavorable Gleason score (4 + 4), with present infiltration of tumor cells in peritumoral tissue (lymphatic, vascular and combined) and in patients with high tumor volume. Conclusion. PC patients without any histopathological signs of tumor invasion before the therapy have significantly increased serum IL-10 concentration compared to those with the signs of tumor invasion. There is a clear dissociation of IL-10 values between a serum sample and local, urine and pms samples from a particular patient. After the therapy, high IL-10 serum concentration is present only in patients with high Gleason score, present infiltration of peritumoral tissue and high tumor volume.